Determinants of the decision to grant KUR to MSMEs in Malang City in 2022 - Feri, Riyanto Dwi; Muhammad, Naufal Dzakwana; Rosyada, Fina (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2024)
Provision of People's Business Credit (KUR) to MSMEs facilitates business development. However, in providing KUR, banks must not ignore KUR distribution because banks are very careful in this regard to avoid unwanted things such as default or bad credit. Several factors must be considered by banks when offering KUR. This study aims to identify the determinants of KUR granting to MSMEs in the city of Malang. Respondents in this study were business entities or MSME owners in Malang City. This study uses the variables income, age of business, security, education, financial reports and cultural characteristics. The type of research used is mixed methods. Logistic regression analysis was used to test the hypothesis of this study. Based on the results of the study it is known that income has a positive and significant effect on the decision to grant KUR. Business age has a negative and significant effect on the decision to grant KUR. insurance and education do not affect the decision to grant KUR. Financial statements have a positive and significant effect on the decision to grant KUR. Cultural characteristics have a positive and significant effect on the decision to grant KUR.